Estimation of effectiveness of aircraft functional system - Ліннік, І.І.; Тамаргазін, О.А. (Proceedings of National Aviation University (archive), 2004)
It is discussion the problem of an estimation of effectiveness engineering systems at construction of polystructural model its reliability. It is considered the algorithm of disclosing of a structural functional system determinant in a symbolical aspect.